2020
DOI: 10.1002/ange.202000269
|View full text |Cite
|
Sign up to set email alerts
|

High Ethylene Selectivity in Methanol‐to‐Olefin (MTO) Reaction over MOR‐Zeolite Nanosheets

Abstract: Precisely controlled crystal growth endows zeolites with special textural and catalytic properties. A nanosheet mordenite zeolite with a thickness of ca. 11 nm, named as MOR‐NS, has been prepared using a well‐designed gemini‐type amphiphilic surfactant as bifunctional structure‐directing agent (SDA). Its benzyl diquarternary ammonium cations structurally directed the formation of MOR topology, whereas the long and hydrophobic hexadecyl tailing group prevented the extensive crystal growth along b axis. This kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 39 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…This allows resolving short-range (<1 nm) inter- actions between 29 Si and 1 H spins. [66][67][68] The 29 Si projection of the spectrum in Fig. 12a contains two main peaks around −106 and −113 ppm, which are due to Q 4 (1Al) and Q 4 (0Al) zeolite framework species, 57 respectively.…”
Section: Crystallization Processmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows resolving short-range (<1 nm) inter- actions between 29 Si and 1 H spins. [66][67][68] The 29 Si projection of the spectrum in Fig. 12a contains two main peaks around −106 and −113 ppm, which are due to Q 4 (1Al) and Q 4 (0Al) zeolite framework species, 57 respectively.…”
Section: Crystallization Processmentioning
confidence: 99%
“…13a exhibit a strong signal at ∼54 ppm assigned to tetrahedrally coordinated Al species in the zeolite framework (Al F ), while the presence of a comparatively weak signal at ∼0 ppm is attributed to extraframework Al species in octahedral coordination. 21,67 Deconvoluting these spectra shows that most Al atoms are incorporated into the zeolite framework (Table S8 †). The Si coordination environ-ment was studied by 29 Si MAS NMR spectroscopy.…”
Section: Aciditymentioning
confidence: 99%
“…Mordenite (MOR) is one of the most frequently used and studied zeolite catalysts, which is characterized by its unique texture structure of interconnected elliptical 12-membered ring (MR) straight channels (7.0 × 6.5 Å) and flat 8-MR channels (5.7 × 2.6 Å). Owing to the special micropore structures along with the acid sites therein, MOR has found wide applications in heterogeneous catalysis, with representative reactions such as carbonylation of methanol/dimethyl ether (DME) with CO to form acetic acid/methyl acetate, methanol-to-hydrocarbon conversion, , syngas conversion, etc. , …”
Section: Introductionmentioning
confidence: 99%
“…Researchers have devised different methods to rationally control the BAS distribution, such as controlled synthesis methods. ,,, They have also developed postsynthesis treatments including selective Na + exchange of the BAS in the 8-MR, , hydrothermal dealumination , and chemical treatments with acid , or trimethylchlorosilane to eliminate BAS in the 12-MR, etc. Among them, pyridine adsorption has been proved to be a simple but most effective post-treatment method to prepare MOR with BAS only residing in the 8-MR. This is achieved by taking advantage of the size of the basic pyridine molecule which is too large to enter the 8-MR and thus can only titrate BAS in the 12-MR pores. , In fact, in recent years, numerous reports have documented the superior catalytic performance of pyridine-modified MOR (Py-MOR) over its original counterpart (i.e., MOR) in multiple reactions. ,,,, Studies have shown that the catalytic lifetime of MOR in both methanol and DME carbonylation reactions can be significantly prolonged via pyridine modification, during which the coke formation in the 12-MR is effectively prohibited. ,, Meanwhile, Py-MOR has also been applied in methanol conversion reactions and yielded significantly improved selectivity in C 2 –C 4 alkenes, as well as better catalytic stability compared to parent MOR, though the conversion is slightly compromised .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their high accessibility and diffusibility by large pores, as well as superior selectivity due to medium pores, a CON-type zeolite is expected to be a promising catalyst, especially for the methanol-to-olefins (MTO) reaction, which is considered a clean alternative path to produce light olefins. , An aluminoborosilicate CON-type zeolite, which can be prepared by both postsynthetic modification and direct synthesis to introduce acid sites generated by framework aluminum, has exhibited excellent catalytic performances. Unlike typical zeolites such as ZSM-5, SAPO-34, mordenite, and beta, CON-type zeolites have demonstrated a long catalytic lifetime and high selectivity for key plastic feedstocks such as propylene and butane . However, two significant problems hinder the utilization of CON-type zeolite: (i) a long synthesis duration (7 days) and (ii) a highly expensive OSDA with a complex structure ( N , N , N -trimethyl-(−)- cis -myrtanylammonium (TMMAOH)).…”
Section: Introductionmentioning
confidence: 99%